Reconceptualising quality through pedagogical documentation in early years education in South Africa. - Peers, Joanne (School of Education, 2019)
I invite readers to an interest in re-conceptualise-ing quality through pedagogical documentation in early years education in South Africa. Children in South Africa are entangled in legacies of Western philosophical constructions of being (ontology) and knowing (epistemology) and positioned according to the dominant discourses of the society of which they are a part. It is of concern that in the South African education system, curriculum and classroom environments, children's learning is measured, observed and assessed by pre-determined and fixed westernised performance markers particularly through documentation and the narrow view of quality. I investigate how children are unjustly positioned through what counts as quality in the documenting processes in the early years in South African schools. After the fall of Apartheid in South Africa, political decisions created newer ways of positioning teachers, children and the curriculum in schools. In particular, the pressure for difference in the curriculum design resulted in the state considering a quality education model which could compete with universal views of quality education. In the foreword of the National Curriculum Statement (NCS), Angie Motshekga, the Minister of Basic Education, stated that education and the curriculum play an important role in the realisation of the aims of the constitution. In exploring this issue, I enquire how pedagogical documentation in the context of the Curriculum Assessment Policy Statements (CAPS) of the Basic Education Department can shift children from being otherised to more just ways of repositioning children as co-constructors of theories, thoughts and ideas. The Reggio Emilia approach to education founded by Loris Malaguzzi disrupts the patterns of curriculum and documentation by problematising the limited narrative of who a child is in relation to education. Tracing the messy and unequal relationships that are always present in an early childhood classroom and in the relationships between the human and more-than-human other, how can pedagogical documentation offer an alternative? In particular, I investigate how, through a re-conceptualising of the concept of quality, pedagogical documentation can be used as a tool for the one hundred and a hundred more ways that children learn and relate to human and more-than-human others. I find myself in the messy politics of human exceptionalism in education. I immerse myself in a complex working of broadening meanings and denying defining what it means to participate in research spaces. I present differences, perspectives and theoretical standpoints in paying attention to early years education and look more closely at relationships rather than predictions. Re-storying through following theory, bending theory and transforming theory, I situate this work in an intra-activity of theory and practice. Many tracings, disturbances, fissures and historical relatings revealed in the materiality, writing and data created through this project. As a modest witness I am affected by the decomposing and recomposing of many interruptions and impositions for early childhood theory and practice.